Discussion on the Interpretation of the Word Catalysis Catalyst (London Journal of Engineering Research, 2024)
The classical S-B principle considered by the catalytic academia is inaccuracy. Theoretical analysis can proves that the catalytic cycle does not exist, and the intermediate cannot appear. The fundamental reason leading to the mistake of S-B principle is that the catalyst participates in the catalytic reaction and the basic principle of chemical reaction equilibrium is ignored. Therefore, the S-B principle's interpretation of <Catalysis, Catalyst & gt; does not correspond to the fundamentals of thermodynamics. The interpretation of & quot; Catalysis, Catalyst & quot; possess misleading. The interpretation of & quot;contact action, contact agent & quot; is more reasonable. Catalytic phenomenon is a physical phenomenon, not a chemical phenomenon, the catalyst does not participate in chemical reactions, it is just contact, electron donate-accept cycle, electron orbital repeated deformation - recovery. Chemical Reaction Model Mechanism-CRMM brings confusion and huge losses to the research and production of catalysts.
Keywords: catalysis catalyst cabatier principle boudart principle